1996
DOI: 10.1074/jbc.271.19.11063
|View full text |Cite
|
Sign up to set email alerts
|

Photoaffinity Labeling of the Lutropin Receptor with Synthetic Peptide for Carboxyl Terminus of the Human Choriogonadotropin γ Subunit

Abstract: Human choriogonadotropin (hCG) consists of an alpha subunit and a beta subunit. The existing evidence from various studies using truncation, substitution, synthetic hormone peptides, and hCG crystals suggests that the C-terminal region of the alpha subunit contacts the luteinizing hormone/choriogonoadotropin (LH/CG) receptor and is involved in receptor activation. Despite a deluge of the speculation and the important role of the alpha C-terminal region, direct evidence for its interaction with the receptor has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…First, the glycoprotein hormone binds to the extracellular domain, and distinct portions of the hormone act as agonist on the transmembrane receptor core. This mechanism is supported by studies showing that human choriogonadotropin (hCG) and peptides derived from the hCG ␣-chain can directly activate an LHR mutant that lacks the ectodomain (6,7). Second, the ectodomain of glycoprotein hormone receptors functions as an inverse agonist keeping the TMD region in an inactive conformation.…”
mentioning
confidence: 62%
“…First, the glycoprotein hormone binds to the extracellular domain, and distinct portions of the hormone act as agonist on the transmembrane receptor core. This mechanism is supported by studies showing that human choriogonadotropin (hCG) and peptides derived from the hCG ␣-chain can directly activate an LHR mutant that lacks the ectodomain (6,7). Second, the ectodomain of glycoprotein hormone receptors functions as an inverse agonist keeping the TMD region in an inactive conformation.…”
mentioning
confidence: 62%
“…The CTP of the hCG α-subunit is important in receptor binding and signal transduction [17][18][19][20]. Previously, it has been shown that removal of the O-glycosylated region of CTP from both eLH β [21] and hCGβ [22][23][24][25] either has no effect or leads to enhancement of receptor-binding activity of these modified hormones.…”
mentioning
confidence: 99%
“…Indeed, several studies with single-chain hCG (22,23) and hFSH (35) have now ascribed the primary function of the cystine knot to intracellular behavior and not to productive in vitro bioactivity. First generation yoked hormones were constructed as N-␤-␣-C so as to utilize the CTP of ␤ as a linker and to retain the free C terminus of ␣, which is reported to be important in receptor binding and activation (10)(11)(12)(13). YhCG1 was able to bind to and activate LHR with properties similar to those of the native heterodimer.…”
Section: Discussionmentioning
confidence: 99%
“…It is evident that heterodimerization is a prerequisite for biological activity, and the individual subunits cannot activate LHR (8). The seat-belt loop is intimately involved in conferring specificity (9), and the C terminus of ␣ is important in high-affinity receptor binding and activation (10)(11)(12)(13). These critical regions are located on one face of the hormone (4,5), which carries a net positive surface charge that is complementary to the receptor's net negative surface charge reported in several homology models of the extracellular domain (14,15).…”
mentioning
confidence: 99%